Analyzing The Relationship Between Motivation and Sportsmanship Among Rugby Athletes - Iman Zulhaqim Mohd Julaimi; Kamal, Azlan Ahmad (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2024)
The purpose of this study is to examine how UiTM Puncak Alam rugby players' motivation and sportsmanship relate to one another. Data were gathered from 108 chosen rugby players using the Multidimensional Sportspersonship Orientations Scale (MSOS-25) and the Sport Motivation Scale (SMS-II). The results show that intrinsic and extrinsic motivational factors both play important roles in the major influence of motivation on sportsmanship conduct. Intrinsic motivation strengthens a sincere regard for the game, whereas extrinsic incentive—such as prizes and recognition—promotes sportsmanship by encouraging fair play and moral behaviour. According to normality tests, the data had an approximate normal distribution and were suitably distributed, with skewness and kurtosis values falling within acceptable bounds. These findings point to an evenly distributed motivating climate among the athletes. By shedding light on the many motivating variables that affect sportsmanship, the study helps coaches, educators, and sports psychologists improve their athlete development initiatives. Furthermore, sustaining high standards of sportsmanship depends on striking a balance between internal and extrinsic incentive. A heavy dependence on outside incentives might compromise true sportsmanship, yet a strong internal drive promotes morality and reverence for the game. The results underscore the significance of devising motivating tactics that include intrinsic and extrinsic components to foster comprehensive athlete growth. It is advised that further study be done to examine the long-term impacts of these motivating techniques on sportsmanship and performance in many sporting situations. This might result in the creation of athlete development and training programs that are more successful.